PERSON-CENTRIC CARE OF ELDER MISTREATMENT: LESSONS LEARNED FROM A SERVICE ADVOCATE. (11th November 2018) - Rowan, J; Gassoumis, Z; Homeier, D; Rath, L; Wilber, K
Abstract: Elder mistreatment has enormous costs to victims and society, yet little is known about strategies to effectively prevent and mitigate the effects. Maintenance of decision-making for older people is beneficial for psychological well-being, physical health, and reduced mortality. As such, person-centered approaches are associated with decreased cost and improved patient outcomes in medical treatment of older people. While person-centered practice is also developing in elder mistreatment interventions, no research has studied the process or efficacy. The aim of this paper is examination of structure and function of a Forensic Center Service Advocate (FCSA), an emerging practice designed to advocate for preferences of older adults who are victims of abuse or neglect through case management. The FCSA extends the services of an elder abuse multidisciplinary team, and is referred cases that need care above usual crisis interventions. Content analysis of the FCSA case documentation identifies tasks, role, and purview of the FCSA, informing a Service Advocate Model. Three case studies demonstrate effective brokering between protective goals and client preferences through relationship-building between FCSA and client and, when appropriate, providing services to suspected abusers to promote well-being among caregiver dyads. A key finding is that client preferences seemingly opposing personal safety can be facilitated with case management that prioritizes development of client-case manager rapport to understand client goals, enabling a middle ground between safety and client preference.